Pain as the neglected patient safety concern: Five years on - Twycross, A.; Forgeron, P.; Chorney, J.; Backman, C.; Finley, G. A. (Université d'Ottawa | University of Ottawa, 2016)
Five years ago, we published a commentary in theCanadian Medical Association Journalarguing that inadequately managed pain in children should be considered an adverse event, a harmful patient outcome. We argued that inadequately managed pain meets the definition of an adverse event and further hypothesized that treating pain as an adverse event may improve care by raising health care administrators and quality improvement experts' awareness of this issue. In this article, we reflect on the progress made in both moving this proposition forward and testing out the concept. We then move on to look at what still needs to be done to ensure that children's pain is managed effectively.
Keywords: adverse event; children; paediatrics; pain management